1999
DOI: 10.1159/000029750
|View full text |Cite
|
Sign up to set email alerts
|

Fractionated Stereotactic Radiosurgery for Treatment of Acoustic Neuromas

Abstract: Background: Microsurgery and single-fraction radiosurgery for acoustic neuromas are associated with high rates of control, but can result in facial palsy and trigeminal neuropathy. To reduce the morbidity of treatment for acoustic neuromas while maintaining efficacy, we explored fractionated stereotactic radiosurgery (FSR). Methods: We reviewed data for 31 acoustic neuromas in 30 patients treated with 25 Gy (linear accelerator) given in 5 consecutive daily fractions. The minimum follow-up was 6 months (6–44 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…1,13,14,26,41,55,71,79,83,84 While planning is often similar to GKS, the method of immobilization is different. Rather than a frame-based approach, the position of target structure is replicated daily using customized head molds and/or face masks while obtaining regular radiographs to confirm positioning.…”
Section: Discussionmentioning
confidence: 99%
“…1,13,14,26,41,55,71,79,83,84 While planning is often similar to GKS, the method of immobilization is different. Rather than a frame-based approach, the position of target structure is replicated daily using customized head molds and/or face masks while obtaining regular radiographs to confirm positioning.…”
Section: Discussionmentioning
confidence: 99%
“…1,[11][12][13]28,39,47,55,62,63,[94][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110][111][112] The age range of patients treated with radiosurgery varied from 20 years to 73.5 years, with an average of 53.6 years (±10.7 years) and an average follow-up time of 41.2 months (±27.1 months). Similarly, the median length of follow-up in our analysis was 34.3 months.…”
Section: Systematic Analysismentioning
confidence: 99%
“…Similar results have been confirmed in other patient series. 2,6,10,15,21,29,48,49,55 Sheehan and colleagues 45 have reported excellent results using GKS in 26 patients with trigeminal schwannomas, and Hasegawa and associates 14 found similar results in 37 patients. Kida et al 18 reported a 100% tumor control rate of facial neuromas after a mean follow-up of 31 months with GKS.…”
Section: Schwannomasmentioning
confidence: 96%